A randomized double-blind, placebo-controlled trial of minocycline in children and adolescents with fragile x syndrome - Leigh, Mary Jacena S; Nguyen, Danh V; Mu, Yi; Winarni, Tri I; Schneider, Andrea; Chechi, Tasleem; Polussa, Jonathan; Doucet, Paul; Tassone, Flora; Rivera, Susan M; Hessl, David; Hagerman, Randi J (Journal of developmental and behavioral pediatrics, 2013)
Minocycline rescued synaptic abnormalities and improved behavior in the fragile X mouse model. Previous open-label human studies demonstrated benefits in individuals with fragile X syndrome (FXS); however, its efficacy in patients with FXS has not been assessed in a controlled trial. Randomized, double-blind, placebo-controlled, crossover trial in individuals with FXS, aged 3.5 years to 16 years (n = 55, mean age 9.2 [SD, 3.6] years). Participants were randomized to minocycline or placebo for 3 months and then switched to the other treatment. Sixty-nine subjects were screened and 66 were randomized. Fifty-five subjects (83.3%) completed at least the first period and 48 (72.7%) completed the full trial. Intention-to-treat analysis demonstrated significantly greater improvements in one primary outcome, Clinical Global Impression Scale-Improvement after minocycline compared with placebo (2.49 ± 0.13 and 2.97 ± 0.13, respectively, p = .0173) and greater improvement in ad hoc analysis of anxiety and mood-related behaviors on the Visual Analog Scale (minocycline: 5.26 cm ± 0.46 cm, placebo: 4.05 cm ± 0.46 cm; p = .0488). Side effects were not significantly different during the minocycline and placebo treatments. No serious adverse events occurred on minocycline. Results may be potentially biased by study design weaknesses, including unblinding of subjects when they completed the study, drug-related side effects unblinding, and preliminary efficacy analysis results known to investigators. Minocycline treatment for 3 months in children with FXS resulted in greater global improvement than placebo. Treatment for 3 months appears safe; however, longer trials are indicated to further assess benefits, side effects, and factors associated with a clinical response to minocycline.